SURVEY ON IODINE CONTENT OF SALT CONSUMED IN TEHRAN AND THE EFFECT OF HEAT, LIGHT AND MOISTURE ON ITS CONTENT - M. Kimiagar; A. Motiee; Sh. Zekavati (Tehran University of Medical Sciences, 1998)
Iodine deficiency disorders are among the most important health problems in Iran. Use of iodized salt is one of the oldest, most convenient and cheapest ways of IDD control, although not very easy to implement. Factors such as the chemical form of iodine, heat moisture, light and storage affect its stability. In this survey, salt iodine content at production site and the effect of heat, moisture and light on salt produced in 6 factories in Tehran were measured in May 1994. The results showed that salt iodized with potassium iodated at 40 ppm and stored for 15 days in favorable conditions, kept over 90% of its iodine content. Keeping the salt in solution form for 3.5 h resulted in 5% reduction of the iodine (P